Eksplorasi Dinamika Gender dan Pubertas Remaja Perempuan dalam Film Tiger Stripes - Pebryan Jaya, Eko; Febrian Jaya, Eko; Pratiwi, Feny selly (Center of Gender Studies and Child of State Islamic Institute of Metro, 2024)
Film is a medium that can offer a unique perspective on various realities around us. Tiger Stripes is a film from Malaysia which tells the story of a teenage girl who experiences physical and emotional changes during puberty in the horror drama genre. This research aims to analyze how gender dynamics and the experience of puberty are represented in films. Through Roland Barthes' semiotic analysis to explore the various meanings behind film visuals and narratives, from the level of denotation, connotation and myth. The research results show that Tiger Stripes not only depicts the biological changes experienced by the main character, but also psychologically in dealing with environmental responses which are socially constructed as gender biased. The use of natural and supernatural elements creates tension between individual identity and normative social expectations. Additionally, Tiger Stripes effectively uses signs to build a narrative that challenges gender stereotypes and puberty in teenage girls. So this gives room for a more complex interpretation of female puberty. This research not only contributes to the understanding of gender representation in the media, but also serves as a medium for criticism of the social norms that shape the identity of teenage girls. Keywords: Exploration, Gender Dynamics, Puberty, Film, Tiger StripesAbstrakFilm merupakan medium yang dapat menawarkan perspektif unik tentang berbagai realitas sekitar kita. Tiger Stripes adalah film asal Malaysia berkisah tentang seorang remaja perempuan yang mengalami perubahan fisik dan emosional selama masa pubertas dalam balutan genre drama horor. Penelitian ini bertujuan untuk menganalisis bagaimana dinamika gender dan pengalaman pubertas direpresentasikan dalam film. Melalui analisis semiotika Roland Barthes untuk mengeksplorasi berbagai makna di balik visual dan narasi film, dari level denotasi, konotasi, dan mitos. Hasil penelitian menunjukkan bahwa Tiger Stripes tidak hanya menggambarkan perubahan biologis yang dialami oleh tokoh utama, tetapi juga psikis dalam menghadapi respon lingkungan yang secara konstruksi sosial digambarkan bias gender. Penggunaan elemen-elemen alam dan supranatural, menghadirkan ketegangan antara identitas individu dan harapan sosial yang normatif. Selain itu, Tiger Stripes secara efektif menggunakan tanda-tanda untuk membangun narasi yang menantang stereotip gender dan pubertas pada remaja perempuan. Sehingga hal tersebut memberi ruang bagi interpretasi yang lebih kompleks tentang pubertas perempuan. Penelitian ini tidak hanya memberikan kontribusi pada pemahaman tentang representasi gender dalam media, namun juga menjadi medium kritik terhadap norma-norma sosial yang membentuk identitas perempuan remaja.Keywords: Eksplorasi, Dinamika Gender, Pubertas, Film, Tiger Stripes